SWITCHING CONTROL MODEL FOR A FIVE-LEVEL H-BRIDGE/NEUTRAL POINT CLAMPED (H-NPC) INVERTER USING SINUSOIDAL PULSE WIDTH MODULATION (SPWM) TECHNIQUES - MAHMUD, ISMAILA (2013)
High power demand give rise to emergence of multilevel inverters in large electric drives and utility application. The structure of multilevel inverters has the ability to reduce harmonics and improve power rating performance. The development of a good switching control is necessary for the operation of the multilevel inverter.